O Pará que «Treme»: Compreendendo o Tecnobrega como Património Cultural Imaterial - Fernandes, Mariana Beatriz Marques (CEM – Cultura, Espaço & Memória, 2021)
The Tecnobrega as a characteristic musical rhythm and cultural heritage of the state of Pará (Brazil), carries with it several elements that express the identity of the community to which it belongs and which involve not only its melody, but also its parties, environments, agents, dances, gestures and symbols. This work aims to, as an introductory way, identify these elements and to understand their role in the formation of this property and in its process of patrimonialisation, as well as to suggest measures for its recognition, preservation and valorization through educational measures.